An Overview of Alkylresorcinols Biological Properties and Effects - Anastasia A. Zabolotneva; Olga P. Shatova; Anastasia A. Sadova; Aleksandr V. Shestopalov; Sergei A. Roumiantsev (Journal of Nutrition and Metabolism)
The investigation of alkylresorcinols has drawn an increasing interest recently. Alkylresorcinols (ARs) are natural chemical compounds synthesized by bacteria, fungi, sponges, and higher plants, possessing a lipophilic polyphenol structures and a myriad of biological properties. Human takes ARs as a component of a whole grain diet (from whole grain rye, wheat, and barley products), and thus, alkylresorcinols are frequently used as whole grain intake markers. Besides, ARs are considered as promising bioregulators of metabolic and immune processes, as well as adjuvant therapeutic agents for antimicrobial and anticancer treatment. In this review, we attempted to systematize the accumulated information concerning ARs origin, metabolism, biological properties, and their effect on human health.